Dancing Youth : Hip Hop and Gender in Late Socialist Vietnam - Kurfürst, Sandra (Global studies (Bielefeld, Germany), 2021)
Breaking, popping, locking, waacking, and hip hop dance are practiced widely in contemporary Vietnam. Considering the dance practices in the larger context of post-socialist transformation, urban restructuring, and changing gender relations, Sandra Kurfürst examines youth's aspirations and desires embodied in dance. Drawing on a rich and diverse range of qualitative data, including interviews, sensory and digital ethnography, it shows how dancers confront social and gender norms while following their passion. As a contribution to area and global studies, the book illuminates the translocal spatialities of hip hop, produced through the circulation of objects and the movement of bodies.